2019
DOI: 10.1002/lary.28344
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in HPV‐Associated Oropharynx Carcinoma Treated With Surgery Alone

Abstract: Objective Survival outcomes for human papillomavirus‐associated oropharynx squamous cell carcinoma (HPV + OPSCC) treated with surgery alone are unclear. To increase understanding, we assessed overall survival (OS) outcomes using the national cancer database (NCDB). Methods We conducted a retrospective analysis of OS of 736 NCDB HPV + OPSCC patients who underwent surgery alone from 2010 to 2014 using univariate and multivariate analyses and the Kaplan‐Meir method. Results Multivariable analysis found the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
1
22
1
Order By: Relevance
“…The association of LVI with poorer survival for the S + CRT group may warrant additional attention. Prior NCDB studies of HPV-related OPSCC did not find an association between LVI and poorer survival in low-risk/surgery-alone cohorts, 30,31 which are distinct from the S + CRT cohort of this study. Studies with larger HPV-related OPSCC NCDB cohorts did not examine LVI as a risk factor.…”
Section: Discussioncontrasting
confidence: 65%
“…The association of LVI with poorer survival for the S + CRT group may warrant additional attention. Prior NCDB studies of HPV-related OPSCC did not find an association between LVI and poorer survival in low-risk/surgery-alone cohorts, 30,31 which are distinct from the S + CRT cohort of this study. Studies with larger HPV-related OPSCC NCDB cohorts did not examine LVI as a risk factor.…”
Section: Discussioncontrasting
confidence: 65%
“…Han et al compared the 7th and 8th editions in a study involving 736 HPV-positive patients with OPSCC. When the 7th edition criteria were applied, they found no differences in OS among stage pN0, pN1 and pN2 patients [ 20 ]. Considering the findings described above, there was a clear, urgent need to re-evaluate and modify the staging system in the 7th edition to include HPV status, which would help to ensure adequate discriminative power between the different stages.…”
Section: The 7th Edition Of the Ajcc Staging System: A Need For Changmentioning
confidence: 99%
“…In 2019, Han et al published a retrospective analysis of 736 patients with only surgically treated HPV-positive OPSCC from the NCDB (2010-2014) (43). Among other things, they showed that microscopic or macroscopic ENE results in a significantly worse OS when compared to positive lymph nodes without ENE (5J-OS: 91% vs. 78%; p < 0.0001) (43).…”
Section: Extranodal Extension In the Context Of The 8th Uicc Classifimentioning
confidence: 99%
“…In 2019, Han et al published a retrospective analysis of 736 patients with only surgically treated HPV-positive OPSCC from the NCDB (2010–2014) ( 43 ). Among other things, they showed that microscopic or macroscopic ENE results in a significantly worse OS when compared to positive lymph nodes without ENE (5J-OS: 91% vs. 78%; p < 0.0001) ( 43 ). In addition, Freitag et al recently published their analysis of a cohort of 92 patients with surgically treated HPV-mediated OPSCC (IC+OP+RT: n = 8, OP: n = 21, OP+RT: n = 23, OP+RCT: n = 39, OP+RT+Cetuximab: n = 1) ( 44 ).…”
Section: Extranodal Extension In the Context Of The 8th Uicc Classifimentioning
confidence: 99%